(untitled) (Global Conference on Medical and Health Sciences, 2026)
Neuroinflammation has emerged as a central biological process underlying a wide range of neurological and psychiatric disorders, including Alzheimer’s disease, Parkinson’s disease, multiple sclerosis, depression, and schizophrenia. Traditionally viewed as distinct clinical entities, these disorders are increasingly recognized to share common inflammatory pathways involving microglial activation, cytokine dysregulation, and disruption of the blood–brain barrier. Understanding neuroinflammation as a convergent mechanism provides new opportunities for integrated diagnostics and targeted therapeutic interventions. This study explores the role of neuroinflammatory processes as a shared pathophysiological pathway across neurological and psychiatric conditions, adopting a translational perspective that links molecular mechanisms to clinical manifestations. A comprehensive analytical approach was employed, synthesizing findings from recent advances in neuroimmunology, molecular neuroscience, and clinical research.